NILAI-NILAI PENDIDIKAN KARAKTER DALAM GAGURITAN WATUGANGGA - Ni Putu Gatriyani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Gaguritan Watugangga is one of the literary works full of with the value of character education. However, the lack of public knowledge against geguritan causes this geguritan not to be familiar among the people Balinese people. The purpose of this research is to describe the formal structure, narrative structure and character education values contained in the in Gaguritan Watunggangga. This type of research is literary research, with an intrinsic approach and mimesis. The types of data collected are primary data and secondary data with qualitative data. While the method used in data collection is a method of recording documents. Data analyzed by descriptive method with induction and argumentation techniques. Based on the discussion of the research results, it is concluded that: 1) The formal structure in Gaguritan Watugangga, namely: (1) the literary code that building Gaguritan Watugangga is a pupuh of 75 stanzas consisting of 8 (eight) types of pupuh, namely Pupuh Sinom, Pupuh Ginada, Pupuh Semarandana, Pupuh Pucung, Pupuh Pangkur, Pupuh Durma, Pupuh Ginanti, and Pupuh Maskumambang; (2) the variety of languages used, namely Kawi and Balinese language (basa jabag rough, base andap, base alus sor, and base alus singgih); and (3) language style consists of affirmative figure of speech (tautology and esclamation) and comparative figure of speech (hyperbole). 2) Narrative structure in Gaguritan Watugangga, namely: (1) a synopsis (Telling about the Watugangga who looking for his father named Sang Anoman); (2) the theme is a child who is looking for his father; (3) characters and characterizations, namely Sang Watugangga (a human fish, handsome, dignified, brave, honest, and responsible), Sang Rama (a king who is patient, noble and forgiving), Sang Anoman (faithful, obedient, hardworking and powerful), Mother Sang Watugangga (a big fish, dear and loves his son), Detya Narayama (a cunning giant, agitator and a liar), and Sang Sugriwa (a loyal, obedient and ape-man respect for the leader); (4) the grooves used are mixed grooves; (5) background, namely in Mount Himawan, Tasiktala, Ganges River, forest, Cretatala, Mount Swela, and the road; (6) mandate, which is selective in making friends, don't arrogant, think before doing something, and stay calm in the situation however. 3) The value of character education contained in Gaguritan Watunggangga, namely: religious values, discipline, hard work, curiosity, honesty, friendship, peace-loving, and tolerance